Measuring the natural radioactivity samples of some domestic wheat flour and comparing it with some imported wheat flour for Iraqi markets using gamma-ray spectroscopy - Zainab K. Nasser Allah; Essam M. Rasheed; Ammar A. Al Rawi (Iraqi Journal of Physics)
In this study, twenty samples of wheat flour were collected from local markets. Thirteen of these samples were local flour with different commercial names, and seven were imported flour with different commercial names. Three radionuclides (U-238, Th-232, K-40) were detected in all the wheat flour samples with a multichannel buffer (MCB) detector. The value of the specific activity of the local flour for the element U-238 ranged between 4.34 and 11.88 Bq/kg, with an average value of 7.98 Bq/ kg, as for the element Th-232, its specific activity ranged between 3.22 and 4.84 Bq/ kg, with an average value of 3.94 Bq/kg. For the element potassium K-40, the specific activity ranged between 220.45 and 290.65 Bq/kg with an average value of 248.63 Bq/kg. The average specific activity of imported flour for the element uranium U-238 ranged between 1.25  and 4.38 Bq/ kg, with an average value of 2.48 Bq/kg. As for the element Th-232, its specific activity ranged between 0.22 and 2.88 Bq/kg, with an average value of 1.51 Bq/ kg. As for the element potassium K-40, its specific activity ranged between 152.23 and 161.32 Bq/ kg with an average value of 158.19 Bq/kg. The radioactivity dose calculated for all samples is 0.424 mSv.y-1, which is lower than the allowable limit of 1 mSv.y-1. It was shown through this study that the radioactivity level of local flour was higher than that of imported flour.